Program Pendampingan Berbasis Herbal untuk Pencegahan Anemia pada Remaja Putri di SMAN 4 Muaro Jambi - Amraini Amelia; Chindiana Khutami; Yesi Mustika Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Anemia is a health problem that requires special attention, especially among adolescents, due to its high prevalence and harmful impact on future generations. Data from Riskesdas 2018 shows that the prevalence of anemia in Indonesia is 26.8% in children aged 5-14 years and 32% in those aged 15-24 years. This community service program aims to prevent anemia and improve food security among adolescents at SMAN 4 Muaro Jambi through preparation, socialization, training, technology implementation, mentoring, and evaluation phases. The methods used include counseling, cadre training, and herbal product creation. Mandatory outputs include activity videos, media publications, and increased partner knowledge, along with additional outputs such as a guidebook and scientific articles. Significant results from this program include increased adolescent knowledge about anemia prevention and food security, cadre training for simple Hb level checks, and training on making simple herbal products for anemia prevention, such as lemongrass butterfly pea flower tea, roselle tea, and turmeric tamarind herbal drink. This program is expected to serve as a model for other schools and help reduce the prevalence of anemia in Jambi Province.